INTRODUCTION AND SELECTION OF TREE-LIKE PAEONS IN THE SOUTH URAL BOTANICAL GARDEN-INSTITUTE OF UFRC RAS (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2022)
The article presents data on the study of biological and morphological characteristicsof 15 varieties of tree paeonia during introduction in the conditions of the forest-steppe zone of theBashkir Cis-Ural. Quantitative and qualitative features were analyzed. Their research was carriedout in accordance with the «Test methodology for distinctness, uniformity and stability». Thephenotypic variability of quantitative parameters was studied. A positive high correlation wasnoted between the flower diameter and the length of the longest tepal. The revealed patterns are ofinterest for building a model of paeony varieties and using them in plant breeding.
Keywords: varieties of tree paeony; variability; correlation coefficient; botany; introduction.